Pentingnya Pendidikan Karakter Terhadap Pembentukan Moral Anak Sekolah Dasar - Dwi Putri Dina Saharani; Hilda Rahmayani; Pipi Anggreini Putri; Siti Rahmayani (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
The purposes of this research is to determine the importance of character education in the moral formation of elementary school children. This research is a type of qualitative research using library research methods, namely by collecting information through various sources such as journals, books and previous research. The results of this research are that character education has a very important role in shaping the morals of elementary school children.